(untitled) (Tanzania Medical Journal, 2015)
Background: Management of acute surgical abdominal emergencies in children is challenging accounting for significant morbidity and mortality. The latter can be overcome by making a prompt diagnosis so that appropriate treatment can be initiated at the primary health facility and then referred to a specialized centre for further management including surgery.Objective: The aim of this study was to examine the causes and clinical outcomes in children (>30days-10 years) with acute abdomen requiring surgical intervention at Muhimbili National Hospital, (MNH).Methodology: Data was prospectively collected on all children aged between one month and ten years who underwent surgery for acute abdominal emergencies at Muhimbili National Hospital for one year from January 2009 to December 2009.Data collected were patient’s profile, duration of symptoms, clinical diagnosis, clinical outcomes, period of hospitalisation and reasons for delayed presentation to Hospital (MNH). Data analysis was done using the computer program EPI info version 6.Results: A total of 97 children were recruited into the study. 62 were boys (64.0%) and the male to female ratio was 1.8:1. The mean age at presentation was 4.4years (SD ± 3.4).Intestinal obstruction was seen in 58 cases and was the leading cause of abdominal surgical emergency (59.8%). Other causes included 14 cases of abdominal trauma (14.4%), 13 children with peritonitis (13.4%) and 12 with acute appendicitis (12.4%). Wound sepsis was the main postoperative complication seen in13cases (13.4%) and 11 children died giving a mortality of 11.3%. Higher mortality was observed in those who were operated for peritonitis (15.4%) and the main reason for delayed presentation to MNH hospital (?3 days of symptoms) was misdiagnosis at the primary health facilities (62.1%).Conclusions and Recommendations: Acute surgical abdomen predominantly occurred in boys and intestinal obstruction was the main cause. Children who presented late to hospital (MNH) had higher morbidity and mortality. Peritonitis was substantially associated with high mortality and misdiagnosis at the initial health facilities was the major cause for delayed referral to hospital from onset of symptoms. Therefore efforts should be made to improve awareness of clinical presentation of acute abdominal conditions in children at both in the local environment and primary health care level to facilitate early presentation and referral to appropriate specialized centres. Substantial improvement of paediatric surgical care is required in terms of personnel like paediatric surgeons, specialized paediatric anaesthesiologists and nurses as well as the availability of surgical and intensive care facilities for children to reduce mortality.